Digital Note Taking: The Use of Electronic Pens with Students with Specific Learning Disabilities. Issue 2 (June 2013) - Belson, Sarah Irvine; Hartmann, Daniel; Sherman, Jennifer
This article describes a study of the use of a digital note-taking technology with high school students with specific learning disabilities. The goal of the project was to understand the degree to which this intervention has the potential to support students' note-taking skills, promote retention of material, and reduce cognitive effort during note taking. The authors offer recommendations for ways in which existing features and uses of this technology can be improved and enhanced. The findings of this research suggest that the use of digital pens can increase the quality of student notes and note-taking strategies. Based on this pilot study, the pens are recommended for use in particular types of course activities for students with language-based learning disabilities.